PENGARUH MEREK, HARGA, PERSONAL SELLING TERHADAP KEPUTUSANPEMBELIAN PRODUK POCARI SWEAT PADA PT. AMERTA INDAH OTSUKA MEDAN - Rafida Khairani; Srihot Laila; Olyvia Hutasoit (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2020)
The purpose of the study was to examine and analyze the promotion and price on purchasing decisions at PT. Amerta Indah Outsuka Medan. The researcher conducted research at PT. Amerta Indah Outsuka Medan. The approach of this research is quantitative research. The nature of this research is explanatory descriptive research. The population in this study were some customers of PT. Amerta Indah Outsuka Medan who made purchases at PT. Amerta Indah Outsuka Medan. The regression model is used to test the hypothesis. The classic assumption test used includes: normality test, multicollinearity test, and heteroscedestity test. This data analysis model uses multiple regression analysis. The results of the study at the same time became the conclusion of the study was a Brand of 2,329 with a significant value of 0.022 partially significant effect on purchasing decisions at PT. Amerta Indah Outsuka Medan. Price amounting to 2,405 with a significant value of 0,018 partially has a significant effect on purchasing decisions at PT. Amerta Indah Outsuka Medan.Personal Selling3,458 with a significant value of 0.001 partially significant effect on purchasing decisions at PT. Amerta Indah Outsuka Medan.